Ecological Protection Reasoning in Exegesis of Qur’an Surah Al-A'raf [7]: 56 in the Medieval Period - Sofyan, Muhammad Ilham; Arifin , Jainul; Nadhiya, Syarifah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
As ecological crises intensify globally, environmental themes have become prominent in contemporary Qur'anic exegesis (tafsir). However, ecological interpretation had its own distinct dynamics during the medieval period, even though environmental degradation was not as severe as in recent decades. The interpretation of nature protection in Qur'an Surah Al-A'raf [7]: 56 reveals diverse understanding among medieval scholars, challenging the notion that pre-modern interpretations were purely fragmentary or ideological. This study addresses two research questions: a) How was Q.S. Al-A'raf [7]: 56 interpreted ecologically in the medieval period? b) What hierarchical environmental ethics emerge from these medieval interpretations? Using qualitative methodology through literature review, this research focuses on the phrase